Self-managed occupational therapy and physiotherapy for adults receiving inpatient rehabilitation ('My Therapy'): protocol for a mixed-methods process evaluation - Sara L. Whittaker; Nicholas F. Taylor; Keith D. Hill; Christina L. Ekegren; Natasha K. Brusco (BMC, 2021)
Abstract Background Process evaluations have been recommended alongside clinical and economic evaluations to enable an in-depth understanding of factors impacting results. My Therapy is a self-management program designed to augment usual care inpatient rehabilitation through the provision of additional occupational therapy and physiotherapy exercises and activities, for the patient to complete outside of supervised therapy. The aims of the process evaluation are to assess the implementation process by investigating fidelity, quality of implementation, acceptability, adoption, appropriateness, feasibility and adaptation of the My Therapy intervention; and identify contextual factors associated with variations in outcomes, including the perspectives and experiences of patients and therapists. Methods The process evaluation will be conducted alongside the clinical and economic evaluation of My Therapy, within eight rehabilitation wards across two public and two private Australian health networks. All participants of the stepped wedge cluster randomised trial (2,160 rehabilitation patients) will be included in the process evaluation (e.g., ward audit); with a subset of 120 participants undergoing more intensive evaluation (e.g., surveys and activity logs). In addition, 24 staff (occupational therapists and physiotherapists) from participating wards will participate in the process evaluation. The mixed-methods study design will adopt a range of quantitative and qualitative research approaches. Data will be collected via a service profile survey and audits of clinical practice across the participating wards (considering areas such as staffing profiles and prescription of self-management programs). The intensive patient participant data collection will involve structured therapy participation and self-management program audits, Exercise Self Efficacy Scale, patient activity logs, patient surveys, and patient-worn activity monitors. Staff data collection will include surveys and focus groups. Discussion The process evaluation will provide context to the clinical and economic outcomes associated with the My Therapy clinical trial. It considers how clinical and economic outcomes were achieved, and how to sustain the outcomes within the participating health networks. It will also provide context to inform future scaling of My Therapy to other health networks, and influence future models of rehabilitation and related policy. Trial registration This study was prospectively registered with the Australian and New Zealand Clinical Trials Registry (ACTRN12621000313831; registered 22/03/2021, http://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=380828&isReview=true ).